Association between age, gender and multimorbidity level and receiving home health care: a population-based Swedish study. (December 2015) - Zielinski, Andrzej; Halling, Anders
Abstract Background Home health care is an important part of primary health care. How delivery of home health care is organised is probably important for sustainability of the healthcare system as a whole. More than 50 % of individuals over 65 years old have multimorbidity, which increases with higher age, also influencing the needs of home health care. Our aim was to study the proportion of the population above 65 years receiving home health care according to age, gender and multimorbidity level. Methods The study population comprised 32, 130 people aged 65 or more, living in Blekinge County in southern Sweden. We analysed data from patient electronic medical records for patients receiving home health care delivered in patients' own homes by nurses, physiotherapists and occupational therapists. We used the Adjusted Clinical Groups Case-Mix System in order to group individuals according to diagnoses into six levels of multimorbidity. In order to analyse the differences between individuals receiving home health care and those who did not, we used Chi squared test. Logistic regression analysis was conducted in order to study how the dependent variable was influenced by the independent variables. Results A total of 7860 (28 %) of the studied population received home health care in 2011. Logistic regression analysis showed that men had 26 % lower odds of receiving home care compared to women (OR = 0.74, 95 % CI 0.69–0.78). There was also a substantial group (22 %) with low multimorbidity level among people receiving home health care. Adjusting for gender and age showed no differences in odds of receiving home health care for patients with lower levels of multimorbidity. However, for patients with higher levels of morbidity the odds increased dramatically for both genders. Conclusion The question of to whom and to what extent home health care should be provided is an important challenge for policy makers. Our results show that there are differences in the use of home health care dependent on gender, age and multimorbidity level, but also that home health care is provided to individuals with low morbidity. Further studies could explain the factors influencing home health care use.